Regulating readers' bodies: a discourse analysis of teachers' body talk. Issue 5 (3rd September 2017) - Lester, Jessica Nina; Gabriel, Rachael
ABSTRACT: In this paper, we report findings from a discourse analysis study of reading instruction in eight primary/elementary school classrooms in the United States. Drawing upon discursive psychology, we specifically examined 96 hours of reading comprehension instruction, with a focus on how teachers talked about the body during the instruction and noted how this gave rise to particular constructions of what it means to be a 'good' reader and/or learner. We discuss two patterns from the analysis of our data, including: (1) emphasized versus embedded physical control as essential to being a 'successful' reader, and (2), implicit physical control and freedom as essential to literacy learning and to students' identities as readers. We conclude by highlighting implications, with a focus on student identity.